NILAI KEARIFAN LOKAL PESANTREN DALAM UPAYA PEMBINAAN KARAKTER SANTRI - Sofyan Sauri (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
The oldest Indonesia Islamic educational institutions until today has a strategic role as one of the institutions of education transformation. This paper attempts to describe the character of the development efforts of the students among the students. Pesantren which is identical with the yellow book in their work have given the considerable influence for Indonesian. Even boarding in method always apply wisdom values ​​lokn applies traditional education pattern surrounding communities. In Indonesia, there are so many boarding schools, which number in the thousands. In general, the existing boarding schools to implement a traditional education and modern education pattern. However, despite the different patterns of educational learning patterns, but in substance likely to have similarity. One thing that does not seem to be separated from the school that the educational pattern using yellow book as a study. This research method is descriptive analysis with a qualitative approach. There are several local moral values ​​that can be used as a boarding school a learning model that can be adopted by our education today, one of which is a pattern of education that emphasizes the moral values ​​of learners. Such as : courtesy, discipline, exemplary, manners, patience and gratitude, cooperation, faith, responsibility, wisdom, faith. If these values ​​can be applied in all lines of education in Indonesia, then bunalah an impossible thing if the country of Indonesia will experience a period of glory in the future.